2022
DOI: 10.3389/fpls.2022.935819
|View full text |Cite
|
Sign up to set email alerts
|

TGA transcription factors—Structural characteristics as basis for functional variability

Abstract: TGA transcription factors are essential regulators of various cellular processes, their activity connected to different hormonal pathways, interacting proteins and regulatory elements. Belonging to the basic region leucine zipper (bZIP) family, TGAs operate by binding to their target DNA sequence as dimers through a conserved bZIP domain. Despite sharing the core DNA-binding sequence, the TGA paralogues exert somewhat different DNA-binding preferences. Sequence variability of their N- and C-terminal protein pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Accordingly, the 3D structure of HaTGA01 in Figure S3 includes all three fundamental structural components integral to sunflower TGA TFs. These encompass the conserved bZIP domain, the highly variable N-terminal region (colored orange), and the C-terminal portion (C-terminal alpha helix), which contains a hypothetical Delay of Germination 1 (DOG1) domain [30].…”
Section: Conserved Motif and Domain Analysis Of The Tga Family Genesmentioning
confidence: 99%
“…Accordingly, the 3D structure of HaTGA01 in Figure S3 includes all three fundamental structural components integral to sunflower TGA TFs. These encompass the conserved bZIP domain, the highly variable N-terminal region (colored orange), and the C-terminal portion (C-terminal alpha helix), which contains a hypothetical Delay of Germination 1 (DOG1) domain [30].…”
Section: Conserved Motif and Domain Analysis Of The Tga Family Genesmentioning
confidence: 99%
“…(2012) observed that transcriptional activity was affected by the spacing and number of TGACG motifs. The promoter FS-(TGACG) 2 , in which an additional TGACG motif was inserted upstream of the original one, exhibited enhanced expression in roots and salicylic acid inducibility ( Kumar et al., 2012 ; Tomaž et al., 2022 ). Synthetic promoters can also be created by reordering and changing the number of CREs in the promoter, thereby increasing the strength of the endogenous promoter.…”
Section: Limitations Overcome By Synthetic Promoters In the Control O...mentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK)- and cyclic adenosine monophosphate (cAMP)-associated molecules represent widespread intracellular signalling pathways that integrate extracellular stimuli, alter the expression and functionality of receptors, and regulate processes such as cell survival and neuroplasticity [ 140 ]. TGA transcription factors are vital regulators of diverse cellular processes which link to hormonal pathways, interacting proteins, and regulatory elements [ 141 ]. In addition, the phytohormones brassinosteroids (BRs) and jasmonates (JAs) also aid in the regulation of plant growth, development, and defensive response [ 142 ].…”
Section: The Potential Of Microbial Biocontrol Agents In the Fight Ag...mentioning
confidence: 99%